IDENTIFIKASI KECOCOKAN MOTIF TENUN SONGKET KHAS JEMBRANA DENGAN METODE MANHATTAN DISTANCE - Ida Bagus Kade Dwi Suta Negara; I Putu Putrayana Wardana (Jurnal Teknologi Informasi dan Komputer, 2021)
ABSTRACTSongket weaving is spread in several regions in Indonesia with different patterns, motifs and characteristics, one of which is Jembrana songket. Jembrana Songket has a distinctive characteristic that is to put forward the original style of Jembrana. As one of the ikat weaving crafts that has unique motifs, many people do not know what Jembrana ikat motifs are like. Besides that, currently there are many songket woven motifs on the market that have similarities to Jembrana songket weaving motifs, making it difficult to distinguish them for the layman. This study tries to identify the suitability of Jembrana typical songket motifs using image pattern recognition models using the manhattan distance method. There are several processes in identifying the matching Jembrana songket weaving motifs with the manhattan distance method, namely: the process of taking an image, the training process, the process of identification, and the process of displaying the results identification. In this application there are several menus, namely the menu of adding songket data to input training data and the menu introduction to songket to identify the suitability of the motif. Testing the accuracy of the system that is made to get results of 88% with the number of True Positive as many as 43 data, as many as 45 True Negative data, as many as 8 False Positive data, and as many as 4 False Negative data.Keywords: Leave, Lecturer, Education Staff, Application.ABSTRAKTenun songket tersebar pada beberapa daerah di Indonesia dengan corak, motif dan ciri yang berbeda-beda salah satunya adalah songket Jembrana. Songket Jembrana memiliki karakteristik khas yaitu mengedepankan corak asli Jembrana. Sebagai salah satu kerajinan tenun ikat yang memiliki motif khas, banyak orang yang belum mengetahui seperti apa motif tenun ikat Jembrana ini. Disamping itu, saat ini banyak motif tenun songket yang beredar di pasaran memiliki kemiripan dengan motif tenun songket Jembrana sehingga sulit membedakannya bagi masyarakat awam. Penelitian ini mencoba mengidentifikasi kecocokan motif songket khas Jembrana menggunakan model pengenalan pola citra menggunakan metode manhattan distance Terdapat beberapa proses dalam identifikasi kococokan motif tenun songket khas Jembrana dengan metode manhattan distance, yaitu : proses pengambilan citra, proses training, proses identifikasi, dan proses menampilkan hasil identifikasi. Dalam aplikasi ini terdapat beberapa menu yaitu menu penambahan data songket untuk menginputkan data training dan menu pengenalan songket untuk identifikasi kecocokan motif. Pengujian akurasi terhadap sistem yang dibuat mendapatkan hasil sebesar 88% dengan jumlah True Positive sebanyak 43 data, True Negative sebanyak 45 data, False Positif sebanyak 8 data, dan False Negatif sebanyak 4 data.Kata Kunci : Image Processing, Manhattan Distance, Songket Jembrana